Dynamic Stabilization for Degenerative Spondylolisthesis and Lumbar Spinal Instability - OHTONARI, Tatsuya (Neurol Med Chir (Tokyo), 2014)
Lumbar interbody fusion is a widely accepted surgical procedure for patients with lumbar degenerative spondylolisthesis and lumbar spinal instability in the active age group. However, in elderly patients, it is often questionable whether it is truly necessary to construct rigid fixation for a short period of time. In recent years, we have been occasionally performing posterior dynamic stabilization in elderly patients with such lumbar disorders. Posterior dynamic stabilization was performed in 12 patients (6 women, 70.9 ± 5.6 years old at the time of operation) with lumbar degenerative spondylolisthesis in whom % slip was less than 20% or instability associated with lumbar disc herniation between March 2011 and March 2013. Movement occurs through the connector linked to the pedicle screw. In practice, 9 pairs of D connector system where the rod moves in the perpendicular direction alone and 8 pairs of Dynamic connector system where the connector linked to the pedicle screw rotates in the sagittal direction were installed. The observation period was 77–479 days, and the mean recovery rate of lumbar Japanese Orthopedic Association (JOA) score was 65.6 ± 20.8%. There was progression of slippage due to slight loosening in a case with lumbar degenerative spondylolisthesis, but this did not lead to exacerbation of the symptoms. Although follow-up was short, there were no symptomatic adjacent vertebral and disc disorders during this period. Posterior dynamic stabilization may diminish the development of adjacent vertebral or disc disorders due to lumbar interbody fusion, especially in elderly patients, and it may be a useful procedure that facilitates decompression and ensures a certain degree of spinal stabilization.